Gaining stakeholder perspectives to shape a produce prescription program to improve maternal and birth outcomes: a qualitative study - Vilme, Helene; Zhang, Fang Fang; O’Tierney-Ginn, Perrie; Sun, Chenchen H.; Anyanwu, Oyedolapo A.; Fahmi, Rukhshan; Folta, Sara C. (Frontiers in Public Health, 2025)
IntroductionNutrition during pregnancy significantly impacts maternal and birth outcomes. A key factor contributing to the rise in adverse maternal and birth outcomes is poor nutrition. Produce prescription programs have the potential to address pregnancy-related adverse outcomes such as hypertensive disorders and gestational diabetes, but scientific evidence is limited.PurposeTo conduct qualitative interviews to gain an in-depth understanding of how, why, and in what context should produce prescriptions be implemented to best meet the needs of pregnant women in a clinical setting.MethodsWe conducted interviews with 11 patients with low incomes and/or experiencing food insecurity and 11 clinic staff from a major metropolitan OB/GYN clinic. Interview questions were designed to understand attitudes toward participating in or helping implement a produce prescription program. We analyzed the data using a deductive qualitative content analysis approach.ResultsBoth patients and clinic staff perceived many benefits to this type of program, including easing financial strain, removing barriers to access, and addressing nutrition security during pregnancy. Both groups described a need to consider participants’ autonomy in the program design. Patients also perceived some drawbacks to the home delivery aspect, such as limited participation by patients due to unstable housing. Staff expressed some concerns about the staff time needed to implement this type of program.ConclusionThere was strong support for produce prescription programs for this population; however, results indicate that they may best meet needs if patient autonomy and delivery-related barriers are considered in the design. Designating screening and enrollment tasks for ancillary staff may facilitate implementation in clinics.